Understanding Anishinaabek G'giikendaaswinmin (knowledge) on N'bi (water), Naaknigewin (law) and Nokomis Giizis (Grandmother Moon) in the Great Lakes Territory for Water Governance - Bell Chiblow, Susan Anne (2022)
The Canadian settler state lacks a gender balance in N’bi governance and decision making. Little documentation articulates Anishinaabek understandings of reconciliation and how reconciliation can assist with reconciling different legal orders and governance structures which includes Nokomis Giizis (grandmother moon). Drawing on Anishinaabek from the Great Lakes territory, this research explores how does Anishinaabek law construct the role of women in N’bi decision making; can the broader discourse in Canada about reconciliation assist with improving humanity’s relationship to N’bi; how can the concept of reconciliation assist with reconciling different legal orders, and governance structures; what are the relationships and responsibilities between Anishinaabek and Nokomis Giizis and how can these relationships inform N’bi governance including women’s roles. This study utilized an Anishinaabek Research Paradigm (ARP) that employs Indigenous Intelligence as a conceptual framework for qualitative Anishinaabek analysis of data throughout the study. G’giikendaaswinmin shared through conversations, key informants and a focus group are provided into three separate manuscripts. Manuscript One: Indigenous Water Governance: Anishinaabek naaknigewin (law) Constructs the Role of Anishinaabek kweok (women) in N’bi (water) Decision Making supports and expands on existing literature of kweok as N’bi carriers with roles and responsibilities to and specific knowledge of N’bi. It demonstrates that men have a role in N’bi governance and reveals how Anishinaabek naaknigewin constructs the role of kweok in N’bi decision making. Manuscript Two: N’bi Can Teach us about Reconciliation demonstrates how N’bi can teach humanity about reconciliation which could address environmental conflict. It reveals that Anishinaabek understanding of reconciliation is different than mainstream society and is about relationships between Anishinaabek and non-Indigenous but also about relationships with N’bi. Manuscript Three: Relationships and ...